2011
DOI: 10.2320/matertrans.m2010327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a High Magnetic Field on Carbon Diffusion in γ-Iron

Abstract: The effect of 12-Tesla high magnetic field on carbon diffusion in -Fe at 1273 K has been investigated using a diffusion couple made by pure Fe and high purity Fe-0.76%C alloy. The results show that the high magnetic field obviously hinders carbon diffusion in the direction perpendicular to the magnetic field direction; while it only slightly enhances the carbon diffusion in the direction parallel/antiparallel to the magnetic field direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…Studies on carbon diffusion in iron under the effect of a relatively large magnetic field (6 T), as compared to this study, revealed that whereas both a uniform and a "positive" magnetic field gradient reduce the diffusion coefficient, a "negative" magnetic field gradient promotes the diffusion of carbon in £-iron. 19,20) Different results were, however, reported by Wang et al 21) in annealed £-Fe samples at 1000°C under a magnetic field of 12 T. These authors found that the diffusion of C is slighlty enhanced when the magnetic field is applied perpendicular to the interface of the diffusion couple whereas it is lacking when the magnetic field is applied parallel to the interface. This behaviour was explained with the model of Zhang et al, 22) where the atoms experience attraction (contraction of the lattice) along the direction of the magnetic field and repulsion (expansion of the lattice) in the normal plane.…”
Section: Discussioncontrasting
confidence: 43%
“…Studies on carbon diffusion in iron under the effect of a relatively large magnetic field (6 T), as compared to this study, revealed that whereas both a uniform and a "positive" magnetic field gradient reduce the diffusion coefficient, a "negative" magnetic field gradient promotes the diffusion of carbon in £-iron. 19,20) Different results were, however, reported by Wang et al 21) in annealed £-Fe samples at 1000°C under a magnetic field of 12 T. These authors found that the diffusion of C is slighlty enhanced when the magnetic field is applied perpendicular to the interface of the diffusion couple whereas it is lacking when the magnetic field is applied parallel to the interface. This behaviour was explained with the model of Zhang et al, 22) where the atoms experience attraction (contraction of the lattice) along the direction of the magnetic field and repulsion (expansion of the lattice) in the normal plane.…”
Section: Discussioncontrasting
confidence: 43%
“…Some authors argued that high magnetic field has the effects on atomic diffusion coefficients in conventional alloys by influencing chemical potential, kinetic factors or electronic behaviours, and the effects are also determined by field directions. [24][25][26] Besides that the activation energy for atomic diffusion may be lowered by magnetic field so that the diffusion in solid metals is consequently enhanced, the activation energy for vacancy formation may also be decreased to some degree, which leads to an increase in vacancy concentration in solid metals aiding diffusion enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…This can be noted from profound examples of electro-magneto-hydrodynamics effects resulted by a rotational field applied into liquid metals, or enhancement effect of atomic diffusion in solid state, on which there are arguments that high magnetic field can accelerate or retard atomic diffusion in solids, depending on magnetic field orientation and magnetic property of elements. [24][25][26] Thus in a diffusional phase transformation of alloys, magnetic field will play an important role kinetically or thermodynamically, in formation of the specific microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…1), the chemical affinity supports the formation of inter-metallic compounds and which is detrimental to weldability. Further, at elevated temperatures, diffusion of carbon into the interface supports the formation of a thin layer of brittle inter-metallic compounds [19]. When the enthalpy of formation of the mating metals is high and negative, the average number of intermediate phases likely to be formed at the interface increases.…”
Section: Formation Of Inter-metallic Compoundsmentioning
confidence: 99%